A Wedge-Shaped Au Thin Film: Integrating Multiple Surface Plasmon Resonance Sensors in a Single Chip and Enhancing the Figure of Merit - Shimizu, Hiromasa; Ogura, Takahiro; Maeda, Takumi; Suzuki, Shogo (Frontiers in Nanotechnology, 2021)
We show here the design, fabrication, and characterization of a wedge-shaped Au thin film with an enhanced figure-of-merit (FOM). This is achieved by using a reflectivity change in an attenuated-total-reflection (ATR) setup by slightly modulating the wavenumber of the surface plasmon polariton by means of the varying thickness of the Au thin film. The wedge-shaped Au thin film is equivalent to multiple surface plasmon resonance (SPR) transducers integrated in a single chip and was fabricated by an electron-beam evaporation process with the position of the shutter controlled during the deposition. The FOM, defined as the difference between the maximum and minimum values of the normalized reflectivity change (R/R) divided by the corresponding difference of the incident angles, was 8.0-times larger than that based on the reflectivity R. Also, we demonstrated that the wedge-shaped Au thin film was able to detect ethanol gas at a concentration of 0.2 %, corresponding to a refractive index change of 2  10-5, without any surface functionalization. Since the sensing signal can be obtained with a single image from the wedge-shaped Au thin film without precise thickness control of the metal thickness, no other materials or modulation equipment is necessary, and the sensing chip can be employed in simple and highly sensitive systems.